Indonesia and ASEAN in the vortex of the Indo-Pacific Geopolitical - Muhammad E. Ekaputra (Budapest International Research and Critics University, 2021)
Since its emergence, the term Indo-Pacific has received attention from various countries, including big countries such as the United States and China where the two countries are competing the race to spread influence and fulfill its interests in the region through military, economic, and other cooperation. Coupled with the emergence of India, this inevitably creates the potential for instability in the region and friction that can lead to conflict. As a country located right in the middle of the Indo-Pacific, Indonesia does not want the political dynamics in the Indo-Pacific to threaten their security and sustainability. Using a multilateralism approach through ASEAN, Indonesia seeks to encourage dialogue within the framework of ASEAN between Indo-Pacific countries based on the ASEAN Way of Viewing the Indo-Pacific (AOIP). This step is expected to create conditions in the Indo-Pacific region so that the geopolitical climate in the Indo-Pacific prioritizes cooperation over competition. In addition, Indonesia also wants to implement the World Maritime Axis agenda where Indonesia is able to become a mediating country in the region that puts forward a constructive approach in dealing with problems.